Age-period-cohort models approaches and analyses with aggregate data - O'Brien, Robert M. (CRC Press, 2014)
Age-Period-Cohort Models: Approaches and Analyses with Aggregate Data presents an introduction to the problems and strategies for modeling age, period, and cohort (APC) effects for aggregate-level data. These strategies include constrained estimation, the use of age and/or period and/or cohort characteristics, estimable functions, variance decomposition, and a new technique called the s-constraint approach.
Includes bibliographical references and index. - Online resource; title from PDF title page (CRCnetBASE, viewed July 30, 2014)
Keywords: Cohort analysis; Age groups -- Statistical models; Mathematical models; Models, Theoretical; Cohort Studies; Analyse par cohorte; Modèles mathématiques; mathematical models; REFERENCE; Questions & Answers